QC milestones : Timeline of events that shaped a great city. (Quezon City, Philippines : Quezon City Public Library, 2017)
This book is lovingly dedicated to our predecessors and past colleagues at the Quezon City Library who have lit the torch of knowledge and wisdom to generations of readers and learners.
1. Early Years -- 2. Nurturing a Young City -- 3. Planting seeds of Hope -- 4. Establishing Law & Order -- 5. Bringing winds of Change -- 6. Reaping Fruits of Progress -- 6. Delivering effective Governance -- 7. Establishing a vision for the future.
Includes bibliographical references.
Keywords: LIBRARY EDUCATION